Chlamydospore Specific Proteins of Candida albicans - Sujata Ingle; Santosh Kodgire; Asha Shiradhone; Rajendra Patil; Gajanan Zore (Data, 2017)
Polymorphic yeast, Candida albicans, forms thick-walled structures called chlamydospores in order to survive under adverse conditions. We present proteomic profile changes occurring during chlamydospore formation. Chlamydospores were induced by inoculating C. albicans cells (grown for 48 h) on rice extract and semisolid agar containing tween 80 (1%), and were overlaid by a polyethene sheet to induce microaerophilic conditions at 30 °C. Proteins extracted from chlamydospores and hyphae (producing chlamydospores) were identified by LC-MS/MS analysis. Present datasets include proteomic data (Swath spectral libraries) of chlamydospores and yeast phase cells, as well as methodologies and tools used for the data generation. Further analysis is expected to provide an opportunity to understand modulations in metabolic processes, molecular architecture (i.e., cell wall, membrane, and cytoskeleton) and stress response pathways leading to chlamydospore formation and thus facilitating survival of C. albicans under adverse conditions.